Identifikasi program pemerintah bagi lansia dikota Pekanbaru - Rusdi Firdaus; Lapeti Sari; Eka Armas Pailis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Being old is a natural phase in life that must be passed. all people in the world, aging means a change either biologically, socially and economically. This leads directly to a variety of problems that must be faced by all parties, both the elderly and even the government itself. The research was conducted in the city of Pekanbaru, the purpose of this study is to identify government programs for the elderly in the city of Pekanbaru. This research was conducted using descriptive methods, namely objects owned by describing the whole, the results of in-depth interviews and observation. Conclusion the government program that is felt by the elderly as a form of address among other issues the elderly, UEP program for the elderly is still productive, home care , trauma center programs, elderly day care, social security programs, meals and assistance, institutional strengthening for social organizations that deal with the elderly.Keywords : Population aging category, program-pogram made by the City of Pekanbaru for the elderly.